Engagement of young immigrants: The impact of prosocial and recreational activities. Issue 4 (2nd October 2022) - Alfieri, Sara; Marzana, Daniela; D'Angelo, Chiara; Corvino, Chiara; Gozzoli, Caterina; Marta, Elena
Abstract: The participation of immigrants in the host community is recognized in the literature as an important protective factor of integration and well-being. Research suggests that there are psychological and social benefits to community engagement, but also differences among forms of participation. The first aim is to compare levels of Sense of Community and Self-esteem in engaged and not engaged immigrant youth. Within the subgroup of engaged youth, the second and the third aims are to identify the differences in self-esteem, sense of community (aim 2), motivations, and barriers (aim 3), of those engaged in prosocial activities and in recreational ones. Participants are 510 Italian immigrant youth aged from 19 to 29 ( M = 23.75, SD = 2.92). ANOVA results show that (1) engaged immigrant youths report higher levels of both Sense of Community and Self-Esteem than not engaged ones; (2) for engaged youth, recreational activities better support these outcomes than prosocial; (3) immigrants youths engaged in prosocial activities reported higher levels of prosocial values than those engaged in recreation activities. These last perceive as barriers the difficulty in the Italian language, not having enough information regarding the volunteer and fear of conflicts more than other groups; those engaged in prosocial activities report health-related problems.